Strengthening the ties between BASF Petronas Chemical Sdn. Bhd. (BPC) and UMP - Nur Laila, Afandi (2018)
Kuantan, 23rd February – An official working visit by BASF Petronas Chemical Sdn. Bhd. (BPC) has taken place at Universiti Malaysia Pahang (UMP) Gambang campus currently. The visit is on the invitation from German Initiative Team of Faculty of Chemical and Natural Resources Engineering (FKKSA). BASF Petronas Chemical Sdn. Bhd. was represented by Operation Director, Mr Jan Peter Bredehoeft, Director, Safety and Environment, EHS & Security Asia Pacific, Mr Ismail Abdullah and Senior Manager, Human Resource Management, Mr Koljit Singh.